A new test device for the study of metal wear in conditioned granular soil used in EPB shield tunneling. (March 2018) - Oñate Salazar, Cristina Gabriela; Todaro, Carmine; Bosio, Federico; Bassini, Emilio; Ugues, Daniele; Peila, Daniele
Highlights: The knowledge of wear induced by soil on an EPB-TBM is a key issue for successful tunneling. In EPB tunnelling the use of conditioning (mainly foam) is part of the excavation process. The wear reduction effect induced by conditioning is not established with universal accepted tests. A laboratory test procedure for wear testing of conditioned soil has been specifically designed. The lab procedure has been tested on hard materials and conventional steel has proven to be feasible. Abstract: The wear phenomenon evaluation in EPB shield tunneling machines is not a simple issue, as a large number of parameters are involved, such as soil and tool material properties, soil conditioning and pressure in the bulk chamber. The evaluation of the influence of these parameters and predicting this influence is a complex task and the research has proposed different test procedures and approaches. In this paper a new procedure for testing wear of tools with an innovative concept and design is presented. The experimental results obtained using conventional steel and hard material tools, tested with natural and conditioned soils, are discussed. The outcomes show the feasibility of the proposed procedure and the quality of the measurements that can be obtained using the proposed wear tool shape.